Assessment of the genotoxic potential of soil-associated DDTs and its metabolites using the Salmonella/microsome assay - Turganova Ronagul; Koishekenova Gulshat; Zaypanova Saule; Delannoy Matthieu; Jurjanz Stefan; Bekmanov Bakhytzhan (BIO Web of Conferences, 2024)
The study aimed to assess the genotoxicity of different DDT contaminated soils (with different amendment types) in benzene extracts. A Salmonella/microsome assay without metabolic activation (-S9) was performed to evaluate the efficiency to initiate the mutations of remediated and non-remediated soils. The number of revertants mutations in his+ in TA100 and TA98 strains were obtained, and compared to soils without DDT, and remediated DDT containing soils. The interpretation of the data suggests that, mutagenic activity was high for the non-remediated soils samples Kyzylkairat and Beskainar, and revealed in the scale as a weak mutagen. Soil samples treated with DARCO, ORBO, Sarg<150μm, and Sarg>150μm in Kyzylkairat and Beskainar exhibited a decreasing level of mutagenic activity, which is in line with the decreased environmental availability in these soil. Overall, the study indicates that strains TA100 and TA98 are valuable tools for rapidly assessing the potential mutagenicity of soil contaminated with OCPs.